Single-fraction SRS and multiple-fraction SRT for brain metastases from colorectal cancer - Li, Yong; Wu, Junlan; Liu, Fenghua; Shao, Xianjun; Liang, Xiaohua; Zhang, Feifei; Meng, Yan; Shen, Meihua; Pan, Mianshun (Frontiers in Oncology, 2022)
Objective: Brain metastasis from colorectal cancer (CRC) is rare. Although stereotactic radiotherapy (SRT) and stereotactic radiosurgery (SRS) are effective treatments for brain metastasis, reports on brain metastasis of CRC are limited. This study compared the efficacy of SRT and SRS for the treatment of brain metastases from CRC and analysed the related factors to reveal the specificity CRC-derived brain metastasis. Methods: A retrospective analysis of 116 patients with brain metastases from colorectal cancer was performed and included 56 patients in the SRT group and 60 patients in the SRS group. The clinical characteristics of the two groups were analysed, and the local tumour control rate, overall survival time and radiation-induced brain injury were compared between the two groups. Results: The objective response rates of the SRT and SRS groups were 76.8% and 66.7%, respectively, while the local control rates at 6 months were 87.5% and 81.6%, respectively, and no significant differences were observed between the groups (P=0.295). The median overall survival time was 10.3 months for all patients and was 10.9 months in the SRT group and 9.8 months in the SRS group, with no significant difference between the groups (P=0.123). A multivariate analysis showed that the main factors of poor prognosis were low GPA score (P=0.002), KRAS mutation (P=0.035), extracranial metastasis (P=0.005) and no bevacizumab treatment (P=0.001). No significant difference was observed in the incidence of acute and late radiation-induced injury between the two groups. Conclusion: Both SRT and SRS are effective methods for the treatment of CRC-derived brain metastases. The simultaneous use of bevacizumab may be one of the most important factors that affects the survival of these patients.